Students' perception of the nature and benefits of learner- centered education and their attitude towards its implementation in IIUM - Konneh, Mohammed M (Institute of Education, International Islamic University Malaysia, 2011)
Using constructivism as its main theoretical background, learner-centered education is a learning model that seeks active participation of learners in the learning process. Similar to any other form of innovation, successful implementation of the model partly requires learners to perceive its nature and benefits positively. Thus, to examine International Islamic University Malaysia (IIUM) students' perception of the nature and benefits of the model, and determine their support for its implementation in the university, a survey was designed to collect data from respondents. This survey consisted of three constructs (nature, benefit and attitude), whose items were drawn from extant literature on learner-centered education. The reliability of the questionnaire was established using Cronbach's alpha value and the data was analysed using cross-tabulation focusing on percentage and chi-square value to see whether or not gender influences the perception of learners towards learner-centered education and their support for its implementation. Findings from the analysis showed that IIUM students perceive the nature and benefit of learner-centered education positively and that they supported its implementation in IIUM.